On the long-run calibration of the credit-to-GDP gap as a banking crisis predictor - Karlo Kauko; Eero Tölö (Bank of Finland, 2019)
The trend deviation of the Credit-to-GDP ratio ("Basel gap") is a widely used early warning indicator of banking crises. It is calculated with the one-sided Hodrick-Prescott filter using an extremely large value of the smoothing parameter λ. We recalibrate the smoothing parameter with panel data covering almost one and a half centuries and 15 countries. The optimal λ is found to be much lower than previously suggested. The 2008 crisis does not dominate the results. The long sample almost eliminates filter initialisation problems.
URN:NBN:fi:bof-201902251071
Keywords: G01; E44; N20; 330